Nano World in Cancer Therapy - Swarna latha, Beesetti (Asian Pacific Journal of Cancer Biology, 2020)
Despite of several pandemic eruptions, cancer still remains the leading cause of death at constant rate. The risk of every alternative disease or disorder increases with the initial incidence of cancer. Cancer treatment has radically changed a lot from conventional therapies like surgery and radiotherapy to targeted therapies like thermal ablation and gene therapy. Deeper knowledge and understanding of key regulators of cancer growth and progression aided in the advancement of cancer therapy. The use of nanoparticles in cancer diagnosis and treatment has gained its importance in the next generation of cancer treatments. Nano oncology enhances the efficacy of chemotherapy for a wide gamut of invasive cancers. Here we provide an overview on the different approaches to treat cancer and discuss the pivotal role of some archetypal cancer therapies and current state and future prospects of diverse biomedical nanomaterials for cancer therapy and imaging.